Injuries in football (soccer)—a systematic review of epidemiology and aetiological aspects - Klein, C.; Henke, T.; Platen, P. (German Journal of Exercise and Sport Research, 2018)
Increasing injury incidences prove the importance of injury prevention in football. The aim of this review was to summarise the recent evidence on the epidemiology and inciting events of acute injuries within subgroups (performance level, age and sex). A systematic literature search was conducted in the databases PubMed, CINAHL, Embase, Cochrane, PEDro, and SPORTDiscus for articles published from 1 January 2014 until 15 October 2017. The search yielded 4690 results. After the initial screening of titles and abstracts, 182 studies underwent detailed full-text screening according to the inclusion and exclusion criteria. Finally, 53 studies were included. Of these, 46 papers contained epidemiological data, with a total of approximately 41,212 observed player seasons and 11 further tournaments, including 7122.5 observed matches with approximately 126,748.5 player hours. A total of 30,844 injuries were identified. The overall injury incidence ranged from 0.6 to 20.3 injuries per 1000?h of exposure. The locations at highest risk of injury were the lower limbs, particularly the thighs, knees and ankles. Injury-inciting events were reported in 12 studies, involving a total of 8035 injuries. Of these 12 studies, 5 considered all body locations, 3 concentrated on anterior cruciate ligament injuries, 1 reported on general head injuries, 2 reported on concussions, and 1 reported on midfacial trauma only. One of the main findings of this review was that playing football does not necessarily imply a high risk of injury. Promising preventive approaches are being used to revise implementation strategies of evident training programmes and management of individual workloads.